2014
DOI: 10.2174/1874149501408010272
|View full text |Cite
|
Sign up to set email alerts
|

Computational Methods for Masonry Vaults: A Review of Recent Results

Abstract: The paper concisely reviews the available numerical methods to analyze masonry vaults up to collapse, putting in evidence pros and limitations of each approach. To be reliable, any procedure adopted should take into account the distinctive aspects of masonry mechanical behavior, namely the scarce (or zero) tensile strength, the good compressive resistance and the observed formation of failure mechanisms constituted by rigid macro-blocks in mutual roto-translation. Classic no-tension material models disregard t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(35 citation statements)
references
References 57 publications
0
34
0
1
Order By: Relevance
“…The mortar is a mix of one part lime and three parts sand, plus water and PVA glue, which creates a sufficient yet weak bond to allow failure to occur along the joints rather than the blocks [28]. Earlier work showed that the weight of the material does not affect the static response of the vault to support spread so there was no need to increase dead load by adding lead weight to simulate self-weight of stone [5], [23], [28].…”
Section: The Modelmentioning
confidence: 99%
“…The mortar is a mix of one part lime and three parts sand, plus water and PVA glue, which creates a sufficient yet weak bond to allow failure to occur along the joints rather than the blocks [28]. Earlier work showed that the weight of the material does not affect the static response of the vault to support spread so there was no need to increase dead load by adding lead weight to simulate self-weight of stone [5], [23], [28].…”
Section: The Modelmentioning
confidence: 99%
“…There does exist a significant amount of analysis tools, techniques, and experimental investigations aimed at the assessment of arches and existing structures (Sarhosis et al 2016b;Tralli et al 2014;Hendry 1998). For earthquake loading, the commonly used techniques are divided into limit analysis (LA) and numerical analyses approaches.…”
Section: Introductionmentioning
confidence: 99%
“…This estimate of r is used in (11) to obtain a new value of reference thrusts that, in turn, is used again in (8) to obtain a new estimate of r. The procedure is iterated until the convergence condition (9) is fulfilled. Finally, at convergence, formula (10) is applied to evaluate actual values of thrust in each branch of the network.…”
Section: Oncet (0)mentioning
confidence: 99%
“…It was recently contributed by O'Dwyer [10] and fully developed by Block and coworkers in recent times [2,3]. Alternative approaches can be found in [1,4,11].…”
Section: Introductionmentioning
confidence: 99%